Research by Geophysical Methods of Hydraulic Structures of Water Management Purpose - Chushkina, Iryna; Maksymova, Nataliia; Pikarenia, Dmytro; Orlinska, Olga (Journal of Lumbini Engineering College, 2022)
Yield growth in the Southern Steppe is impossible without irrigation with the introduction of mineral and organic fertilizers, so the repair, restoration, and construction of new irrigation networks are one of the main tasks of regional and district water management. For the repair of water management networks, regulation of pools of irrigation systems it is necessary to use inexpensive effective methods of the establishment of their technical condition. Such methods are geophysical, which allow to identify the areas of filtration, flooding, violations of protective screens in the control pools of irrigation systems. The necessity of localization of areas of filtration water losses to concentrate repair and restoration works in the most disturbed zones is scientifically substantiated, which will significantly reduce the cost of time and money and increase the overall efficiency of the structure.